Hydrogen ion sensing characteristics of Na3BiO4–Bi2O3 mixed oxide nanostructures based EGFET pH sensor. (24th July 2020) - Sharma, Prashant; Gupta, Sandeep; Singh, Rini; Ray, Kanad; Kothari, S.L.; Sinha, Soumendu; Sharma, Rishi; Mukhiya, Ravindra; Awasthi, Kamlendra; Kumar, Manoj
Abstract: In the present paper, Na3 BiO4 –Bi2 O3 films have been tested for hydrogen ion sensing. Na3 BiO4 –Bi2 O3 mixed oxide nanostructures were deposited on the Indium–Tin-Oxide (ITO) coated glass substrate using a low-cost electrodeposition technique at room temperature. The nanostructures have been characterized using FESEM and XPS to study their morphology and composition, respectively. Vertically aligned nanostructures (thickness~90 nm) with well-defined edges were seen in FESEM studies. XPS analysis indicates the presence of Na3 BiO4 and Bi2 O3 . The crystallinity and the mixed phase of the film were further confirmed by X-ray diffraction study. These nanostructures were explored as a potential candidate for pH sensing using them as a sensing film for Extended-Gate Field-Effect Transistor (EGFET). A sensitivity of 49.63 mV/pH has been observed with good linearity. To the best of our knowledge, for the first time vertically aligned Na3 BiO4 –Bi2 O3 mixed oxide nanostructures are demonstrated as an EGFET-based (Hydrogen ion) pH sensor. Highlights: Na3 BiO4 –Bi2 O3 nanostructured film was deposited by electrodeposition technique. EGFET developed for hydrogen ion (pH) sensing using Na3 BiO4 –Bi2 O3 as sensing film. The pH sensitivity of the film has been found to be 49.63 mV/pH. Higher sensitivity was attributed to the nanostructured film of Na3 BiO4 –Bi2 O3 .